Sing Not War : The Lives of Union and Confederate Veterans in Gilded Age America - Marten, James Alan (Book collections on Project MUSE., 2011)
After the Civil War, white Confederate and Union army veterans reentered--or struggled to reenter--the lives and communities they had left behind. In Sing Not War, James Marten explores how the nineteenth century's ""Greatest Generation"" attempted to blend back into society and how their experiences were treated by non-veterans. Many soldiers, Marten reveals, had a much harder time reintegrating into their communities and returning to their civilian lives than has been previously understood. Although Civil War veterans were generally well taken care of during the Gilded Age, Mar